“Etno Intelligentsia”: Construction of "Lettered Subjects" in Latin America, 1980-2010 [“Etnointelectualidad”: Construcción de “Sujetos Letrados” en América Latina, 1980-2010] - Canales-Tapia, P (Universidad de los Lagos, 2014)
This paper studies the processes of historical social construction of “indigenous intellectuals”, one of the most important and complex stages for ethnic movements in Latin America: redemocratization, the opening of markets and high participation of the grassroots mobilization processes. Thus, this proposition develops a two-point analysis: firstly, the definition and selfdefinition which is made by an indigenous intellectual and, on the other hand, the problems facing this etnointellectual in a scientific and Western semantic framework. © 2014, Universidad de los Lagos. All rights reserved.